g(1)= -2 g(2)= 6 g(n)=g(n−2)⋅g(n−1)​ Find g(3). Show me the solutions and calculations.​

Question

g(1)= -2

g(2)= 6

g(n)=g(n−2)⋅g(n−1)​

Find g(3). Show me the solutions and calculations.​

in progress 0
Khánh Gia 1 day 2021-07-22T16:48:53+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-22T16:50:02+00:00

    Answer:

    g(3) is -12

    Step-by-step explanation:

    Given that

    g(1)= -2

    g(2)= 6

    g(n)=g(n−2)⋅g(n−1)​

    Now the g(3) is

    g(3) = g(3 – 2) . g(3 – 1)

    = g(1).g(2)

    = (-2) (6)

    = -12

    Hence, g(3) is -12

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )